2019
DOI: 10.1002/chem.201904413
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid as an Aryl Radical Inducer in the Gold‐Mediated Arylation of Indoles with Aryldiazonium Chlorides

Abstract: In recent years interestint he development of protocols that facilitate the oxidativea ddition of gold to access mild cross-coupling processes mediated by this metal hasincreased. In this context, we report herein that ascorbic acid, an atural and readily accessible antioxidant, can be used to accelerate the oxidative addition of aryldiazonium chlorides onto Au I .T he aryl-Au III speciesg enerated in this way,h as been used to prepare 3-arylindoles in ao ne-pot protocol startingf rom anilines and para-, meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…319 Indeed, para-nitro and para-benzoyl benzene diazonium chlorides afford the corresponding Au (III) A follow-up study revealed that oxidative addition of aryldiazonium chloride salts to Me 2 SAuCl or Ph 3 PAuCl can be catalyzed by substoichiometric amounts of ascorbic acid as a radical initiator. 320 This strategy was used to develop a stoichiometric arylation of indoles under mild conditions, with a good tolerance of functional groups on both indole and diazonium salt. EPR, DFT and electrochemical studies supported a mechanistic scenario where the oxidative addition occurs through a double one-electron oxidation pathway, where initially the Au(I) precursor is oxidized by an aryl radical to an Au II −aryl species, which then reacts with further diazonium salt to generate the Au III aryl dichloride.…”
Section: Oxidative Addition Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…319 Indeed, para-nitro and para-benzoyl benzene diazonium chlorides afford the corresponding Au (III) A follow-up study revealed that oxidative addition of aryldiazonium chloride salts to Me 2 SAuCl or Ph 3 PAuCl can be catalyzed by substoichiometric amounts of ascorbic acid as a radical initiator. 320 This strategy was used to develop a stoichiometric arylation of indoles under mild conditions, with a good tolerance of functional groups on both indole and diazonium salt. EPR, DFT and electrochemical studies supported a mechanistic scenario where the oxidative addition occurs through a double one-electron oxidation pathway, where initially the Au(I) precursor is oxidized by an aryl radical to an Au II −aryl species, which then reacts with further diazonium salt to generate the Au III aryl dichloride.…”
Section: Oxidative Addition Reactionsmentioning
confidence: 99%
“…A follow-up study revealed that oxidative addition of aryldiazonium chloride salts to Me 2 SAuCl or Ph 3 PAuCl can be catalyzed by substoichiometric amounts of ascorbic acid as a radical initiator . This strategy was used to develop a stoichiometric arylation of indoles under mild conditions, with a good tolerance of functional groups on both indole and diazonium salt.…”
Section: Catalysis-relevant Reaction Stepsmentioning
confidence: 99%
“…Our group has been focused on the development of gold redox processes with aryldiazonium salts. In particular, we have been interested in processes where the diazonium salt is thermally or chemically activated . Initial reports on catalytic redox processes of Au­(I) with aryldiazonium salts required the use of a cocatalyst and light irradiation to promote the formation of Au­(III) species, but later studies manifested that, in some cases, just light, heat, or certain ligands and bases are enough to promote this process. , Recently, we evidenced that ascorbic acid, a natural reducing agent, is able to promote the oxidative addition of Au­(I) with aryldiazonium chlorides, and used this protocol for the arylation of N -methyl indoles .…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to expand our oxidation protocolw ith aryldiazonium chlorides to other transformations of synthetic interest, we decidedt oe xplore the arylationo fN-methylindoles. [59] This time, to accelerate the oxidation step, we examined the effect of adding ascorbic acid or gallic acid, as both compounds have been shown to be able to reduce aryldiazonium salts to aryl radicals. [60] Satisfactorily,w eo bservedt hat ascorbic acid had a notable acceleration effect,r educing the oxidative addition times.…”
Section: Gold(i) Oxidation With Aryldiazonium Salts Promoted By Heatimentioning
confidence: 99%